In commemoration of the eightieth anniversary of the first artificial nuclear reaction realization - Dovbnya, A.N.; Shendryk, V.A. (Вопросы атомной науки и техники, 1999)
In 1919, a distinguished English physicist Earnest Rutherford was the first to observe the nuclear reaction.